2022
DOI: 10.3390/nu14224794
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Urine Metabolites in Healthy Men after Consumption of Acidified Milk and Yogurt

Abstract: The identification of molecular biomarkers that can be used to quantitatively link dietary intake to phenotypic traits in humans is a key theme in modern nutritional research. Although dairy products (with and without fermentation) represent a major food group, the identification of markers of their intake lags behind that of other food groups. Here, we report the results from an analysis of the metabolites in postprandial serum and urine samples from a randomized crossover study with 14 healthy men who ingest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“… 48 It is important to note that the postprandial increase in p -cresol we observed is not specific to the intake of dairy products, as we recently shown that this molecule also increases significantly after the intake of a non-dairy high-fat meal. 49 Furthermore, cresol and phenol are products of the colonic fermentation of dietary proteins that are not produced by the human organism and can be indicative of a protein overload of the small intestine digestive capacity. 50 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 48 It is important to note that the postprandial increase in p -cresol we observed is not specific to the intake of dairy products, as we recently shown that this molecule also increases significantly after the intake of a non-dairy high-fat meal. 49 Furthermore, cresol and phenol are products of the colonic fermentation of dietary proteins that are not produced by the human organism and can be indicative of a protein overload of the small intestine digestive capacity. 50 …”
Section: Resultsmentioning
confidence: 99%
“…48 It is important to note that the postprandial increase in p-cresol we observed is not specific to the intake of dairy products, as we recently shown that this molecule also increases significantly after the intake of a non-dairy high-fat meal. 49 Furthermore, cresol and phenol are products of the colonic fermentation of dietary proteins that are not produced by the human organism and can be indicative of a protein overload of the small intestine digestive capacity. 50 The significantly higher postprandial increase in p-cresol and phenol in the OA population after an identical dairy challenge as the YA is remarkable and may be suggestive of a reduced capacity to digest and assimilate dietary proteins in the small intestine and/or of a difference in the composition of the gut microbiota.…”
Section: Postprandial Age Effect In the Serum Volatilomementioning
confidence: 99%